THE EVOLUTION OF FINLAND’S MILITARY POLICY: TRENDS AND DIRECTION - Sergey N. Grinyaev (Научно-аналитический вестник Института Европы РАН)
The article examines the experience gained by Finland over the two years since it joined NATO. The purpose of the study is to analyse the main steps taken by the country’s military and political leadership in terms of updating the armed forces and integrating them into the Alliance’s structures. The main NATO exercises in which Finland has participated over the past two years are described. The intensity and volume of assistance provided by Helsinki to Ukraine are noted. The role that Finland aspires to play in NATO is its dominance in the Baltic. The reaction of the Russian leadership to the strengthening of the northern flank of the Alliance is outlined. The significance of the study lies in its summarising of the factual basis regarding the key actions of the Finnish leadership in the militarisation of the country, which makes it possible to identify the main trends in Finland’s policy development, which consist in further break in relations with Russia and the militarisation of Finnish society. The practical importance of the study lies in the summarisation and analytical processing of a significant number of sources on Finland’s membership in NATO over the past two years